High Frequency Repetitive Transcranial Magnetic Stimulation Improves Cognitive Performance Parameters in Patients with Alzheimer’s Disease – An Exploratory Pilot Study - Leblhuber, Friedrich; Geisler, Simon; Ehrlich, Daniela; Steiner, Kostja; Kurz, Katharina; Fuchs, Dietmar (Current Alzheimer Research, 2022)
Background: Currently available medication for Alzheimer’s disease (AD) slows cognitive decline only temporarily but has failed to bring about long term positive effects. For this slowly progressive neurodegenerative disease, so far, no disease modifying therapy exists. Objective: The study aims to find out if non-pharmacologic non-invasive neuromodulatory repetitive transcranial magnetic stimulation (rTMS) may offer a new alternative or an add on therapeutic strategy against loss of cognitive functions. Methods: In this exploratory intervention study, safety and symptom development before and after frontopolar cortex stimulation (FPC) using intermittent theta burst stimulation (iTBS) at 10 subsequent working days was monitored as add-on treatment in 28 consecutive patients with AD. Out of these, 10 randomly selected patients received sham stimulation as a control. Serum concentrations of neurotransmitter precursor amino acids, immune activation and inflammation markers, brain-derived neurotrophic factor (BDNF), and nitrite were measured. Results: Treatment was well tolerated, and no serious adverse effects were observed. Improvement of cognition was detected by an increase in Mini Mental State Examination score (MMSE; p<0.01, paired rank test) and also by an increase in a modified repeat address phrase test, part of the 6-item cognitive impairment test (p<0.01). A trend to increase the clock drawing test (CDT; p = 0.08) was also found in the verum treated group. Furtheron, in 10 of the AD patients with additional symptoms of depression treated with iTBS, a significant decrease in the HAMD-7 scale (p<0.01) and a trend to lower serum phenylalanine concentrations (p = 0.08) was seen. No changes in the parameters tested were found in the sham treated patients. Conclusion: Our preliminary results may indicate that iTBS is effective in the treatment of AD. Also a slight influence of iTBS on the metabolism of phenylalanine was found after 10 iTBS sessions. An impact of iTBS to influence the enzyme phenylalanine hydroxylase (PAH), as found in the previous series of treatment resistant depression, could not be seen in our first observational trial in 10 AD patients with comorbidity of depression. Longer treatment periods for several weeks in a higher number of AD patients with depression could cause more intense and disease modifying effects visible in different neurotransmitter concentrations important in the pathogenesis of AD.
Keywords: intermittent theta burst stimulation